Inward rectifier potassium (Kir) current in dopaminergic periglomerular neurons of the mouse olfactory bulb - Borin, Mirta; Fogli Iseppe, Alex; Pignatelli, Angela; Belluzzi, Ottorino (Frontiers in Cellular Neuroscience, 2014)
Dopaminergic (DA) periglomerular (PG) neurons are critically placed at the entry of the bulbar circuitry, directly in contact with both the terminals of olfactory sensory neurons and the apical dendrites of projection neurons; they are autorhythmic and are the target of numerous terminals releasing a variety of neurotransmitters. Despite the centrality of their position, suggesting a critical role in the sensory processing, their properties -and consequently their function- remain elusive. The current mediated by inward rectifier potassium (Kir) channels in DA-PG cells was recorded by adopting the perforated-patch configuration in thin slices; IKir could be distinguished from the hyperpolarization-activated current (Ih) by showing full activation in <10 ms, no inactivation, suppression by Ba2+ in a typical voltage-dependent manner (IC50 208 μM) and reversal potential nearly coincident with EK. Ba2+ (2 mM) induces a large depolarization of DA-PG cells, paralleled by an increase of the input resistance, leading to a block of the spontaneous activity, but the Kir current is not an essential component of the pacemaker machinery. The Kir current is negatively modulated by intracellular cAMP, as shown by a decrease of its amplitude induced by forskolin or 8Br-cAMP. We have also tested the neuromodulatory effects of the activation of several metabotropic receptors known to be present on these cells, showing that the current can be modulated by a multiplicity of pathways, whose activation in some case increases the amplitude of the current, as can be observed with agonists of D2, muscarinic, and GABAA receptors, whereas in other cases has the opposite effect, as it can be observed with agonists of α1 noradrenergic, 5-HT and histamine receptors. These characteristics of the Kir currents provide the basis for an unexpected plasticity of DA-PG cell function, making them potentially capable to reconfigure the bulbar network to allow a better flexibility.